2010
DOI: 10.13031/2013.30080
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Accumulation and Structure in the Flow Path of Drip Emitters Using Reclaimed Wastewater

Abstract: ABSTRACT. Biofouling has been identified as a major contributor to emitter clogging in drip irrigation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This is because wastewater intensifies the potential of microorganisms to develop and produce a biofilm layer on the internal surfaces of a micro-irrigation system. Biofilm formation can result in decreased or uneven discharge and emitter clogging [46]. Similarly, the decrease in uniformity registered in all the emitter models with the increase in the hours of irrigation with regenerated water also coincides with that obtained by other authors [34][35][36]47].…”
Section: Regarding Water Qualitysupporting
confidence: 88%
See 2 more Smart Citations
“…This is because wastewater intensifies the potential of microorganisms to develop and produce a biofilm layer on the internal surfaces of a micro-irrigation system. Biofilm formation can result in decreased or uneven discharge and emitter clogging [46]. Similarly, the decrease in uniformity registered in all the emitter models with the increase in the hours of irrigation with regenerated water also coincides with that obtained by other authors [34][35][36]47].…”
Section: Regarding Water Qualitysupporting
confidence: 88%
“…This is because biofilm formation is a biomass accumulation process that increases with the presence of regenerated water. The formation of the biofilm has different phases, with different structural characteristics, until the development of the biofilm, and there is a relationship between biomass accumulation and clogging in a drip irrigation system receiving reclaimed wastewater [46].…”
Section: Regarding Water Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…flow rate, cross section, and geometry of the millichannel) on microbial composition. Previous studies have described the microbial communities present in biofilms of different drippers by analysing phospholipid-derived fatty acids (PLFAs) (Yan et al, 2010(Yan et al, , 2009Zhou et al, 2017). These authors showed that three to seven types of PLFAs associated with Gram-negative bacteria were common in biofilms inside drippers, suggesting a significant role for these bacteria in biofilm development.…”
Section: Introductionmentioning
confidence: 99%
“…The variation in average flow rate for each type of emitter is calculated by the equation (Yan et al, 2011):…”
Section: Coefficient Of Variation Of Average Flow Rate Dramentioning
confidence: 99%